Microbiomics of Oral Biofilms: Driving The Future of Dental Research - Chaminda Jayampath Seneviratne; Tanujaa Suriyanarayanan (Faculty of Dentistry, Universitas Trisakti, 2017)
Oral infectious diseases such as dental caries, periodontal disease, endodontic infections, oral candidiasis and peri-implantitis cause major health problems worldwide. All of these infectious diseases are associated with the biofilm growth mode of the oral pathogens. In the past, researchers often attempted to examine the association of single pathogens with particular dental diseases such as in the case of Streptococcus mutans acting as an aetiological agent for dental caries and the so-called “red-complex” bacteria for periodontal disease. However, with the recent advent of OMICS biology techniques such as genomics, transcriptomics, proteomics, it is possible to gain new insights into the host-microbial interaction, microbial community structure and composition in the oral cavity. The new studies on oral microbiomics can unravel the facets of the aetiopathology of oral diseases as never seen before. This mini-review will provide an history and overview of some of the existing DNA sequencing platforms employed to study the microbiomics of oral biofilms and the exciting future ahead for dental research.